THE OBLIGATIONS CHILDREN'S LIFE (Fiep Bulletin - online, 2014)
Currently, parents are searching for better conditions of life for their children. This fact provokes the abserve of the family's routine because the parents pass most of the day working and the children expends their time making a lot of activities after school. This way of children's life prevents idleness and collaborates with their development in the future. This children have to follow a busy schedule and because of this, they don't have time enough to play and discover themselves through the tricks. A questionnaire answered for 116 children between 8-11 years old for particular and public schools shows that they have a very busy life and in accordance with some authors we observe as many activities can affect the children's life. The excess in relation to the activities must be controlled considering the stages of growth and the children's development. They have to grow healthful and to acquire knowledge about the most different subjects, but having their limits recognized and respect.